SEROPREVALENCIA DE LA DIROFILARIOSIS Y EHRLICHIOSIS CANINA EN TRES DISTRITOS DE LIMA - Adrianzén G., Jorge (2003)
Canine Heartworm Disease is a parasitic disease caused by the nematode Dirofilaria immitis. The adult forms are found mainly in the pulmonary arteries and the right heart of canids. This nematode is transmitted by intermediate hosts which are blood suckling mosquitoes. Canine Ehrlichiosis is a disease of domestic and wild canids, caused by the rickettsia Ehrlichia canis, that infects mononuclear cells. This microorganism is transmitted by an arthropod vector, the brown dog-tick Rhipicephalus sanguineus. The objective of this assay was to determine the prevalence of Dirofilaria immitis and Ehrlichia canis in dogs of Chorrillos, La Molina and San Juan de Miraflores districts, which are adjacent to naturally stagnated waters. Blood samples were taken from 140 dogs chosen randomly without regard of breed, age and sex from February to May, 2001. The diagnosis was made by the detection of the D.immitis antigen and antibodies against E. canis, using a commercial ELISA kit. The results showed an expected prevalence of 4.4% for D. immitis and 16.5% for E. canis. This study is the first report detecting antibodies against E. canis in Peru.